Challenges and tolerances for a compact and hybrid ultrafast X-ray pulse source based on RF and THz technologies. (July 2020) - Vinatier, T; Assmann, R W; Dorda, U; Lemery, F; Marchetti, B
Abstract: We present an in-depth tolerance study and investigation of the main challenges towards the realization of a hybrid compact ultrafast (fs to sub-fs) X-ray pulse source based on the combination of a conventional S-band gun as electron source and a THz-driven dielectric-loaded waveguide as post-acceleration and compression structure. This study allows us determining which bunch properties are the most affected, and in which proportion, for variations of the parameters of all the beamline elements compared to their nominal values. This leads to a definition of tolerances for the misalignments of the elements and the jitter of their parameters, which are compared to the state-of-the-art in terms of alignment precision and stability of operation parameters. The most challenging aspects towards the realization of the proposed source, including THz generation and manufacturing of the dielectric-loaded waveguide, are finally summarized and discussed.